Dynamic ultraviolet harmonic beam pattern control by programmable spatial wavefront modulation of near-infrared fundamental beam - Won Seungjai; Choi Seungman; Kim Taewon; Kim Byunggi; Kim Seung-Woo; Kim Young-Jin (Nanophotonics)
The ultraviolet (UV) wavelength regime is attracting increasing attention because of its growing demand in semiconductor lithography, spectroscopy, and imaging applications owing to its high spatial resolution and high photon energy. However, beam shape control, beam delivery, and wavefront manipulation of UV laser beams usually require highly dedicated optics because of the strong UV absorption of most optical materials and the high surface precision required for tailoring short wavelengths, thus limiting a broader application of UV wavelengths. Here, we demonstrate a novel dynamic UV harmonic beam pattern control by manipulating the near-infrared (NIR) wavefront of the fundamental wavelength of a femtosecond pulse laser. The temporal and spatial coherences in an optical harmonic generation are known to be well preserved. Therefore, the spatial beam distribution of UV harmonic beams (λ = 400 and 266 nm for second and third harmonics, respectively) could be readily controlled by tailoring the wavefront of the driving infrared (IR) beam, and this approach can be expanded to higher-order harmonics in the vacuum ultraviolet (VUV) or extreme ultraviolet (EUV) regimes. Moreover, this enables fast polarization-sensitive UV beam switching at a speed of 6.7 frames/s in a depth-resolving manner. To efficiently separate the UV beam from the strong fundamental IR background beam, a non-collinear harmonic generation configuration is introduced. This facile dynamic UV beam control technique enables arbitrary wavefront control of UV laser beams for high-precision laser patterning, polarization-sensitive encryption, and 3D holograms.